2017
DOI: 10.1111/1365-2656.12782
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of parasites in food webs using the group model

Abstract: Parasites are ubiquitous and have been shown to influence macroscopic measures of ecological network structure, such as connectance and robustness, as well as local structure, such as subgraph frequencies. Nevertheless, they are often under-represented in ecological studies due to their small size and often complex life cycles. We consider whether or not parasites play structurally unique roles in ecological networks; that is, can we distinguish parasites from other species using network structure alone? We pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Recently in Ecology (26; 27; 28; 29; 30), some authors have suggested the use of statistical methods which jointly infer structural properties and species positions. Originally developed in the field of social sciences (31), Stochastic Block Models (SBM; 32; 33)—also called Group Models in the seminal work by Allesina and Pascual (27)—aim at grouping nodes (species in our case) that are statistically equivalent, “acting” similarly in the network, i.e ., having an equivalent “structural position”.…”
Section: Methodsmentioning
confidence: 99%
“…Recently in Ecology (26; 27; 28; 29; 30), some authors have suggested the use of statistical methods which jointly infer structural properties and species positions. Originally developed in the field of social sciences (31), Stochastic Block Models (SBM; 32; 33)—also called Group Models in the seminal work by Allesina and Pascual (27)—aim at grouping nodes (species in our case) that are statistically equivalent, “acting” similarly in the network, i.e ., having an equivalent “structural position”.…”
Section: Methodsmentioning
confidence: 99%
“…2015 for details and Michalska‐Smith et al . 2018 for updated version of the code). For both the metaweb and each subregion, the algorithm was executed 10 times, each with a random seed, 300 000 MCMC steps and 20 MCMC chains.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, killifish infected with trematodes which encyst their brains were preyed on significantly more frequently by herons, the definitive host, than were uninfected fish [7]. By affecting host population growth and the behaviour of hosts that make them more vulnerable to predation, parasites have important impacts on food webs [15,[122][123][124][125][126], with potentially destabilizing effects for ecosystems. Addressing how behavioural changes owing to parasitic infections at lower trophic levels may affect higher levels of the food chain is therefore important to assess the resilience of an ecosystem to environmental change.…”
Section: (D) Parasite Manipulation Of Host Behaviourmentioning
confidence: 99%